História e memória do Teatro Oficina nos anos 1960 e 1970 - Valentini, Daniel Martins (2017)
Born deepening relations among students of Largo São Francisco, the TeatroOficina belonged to a portion of the middle class that shot radical criticism against capitalism and against imperialist submission that imposed to us great poverty rates and scattered pockets of poverty, through gestated policies by multinational capital and their associateds. The Oficina responded to conservative modernization promoted by the military, exposing the restlessness of a group capable of positioning itself as an important space for an still possible contestation of accelerated capitalism and the imposition of technocratic standards, the suffocation of the freedom of expression and also destruction by cooptation of national culture, which has hit the group, shattering it. With the arrival of counterculture, new young people joined and reoriented the Oficinas’ fight in order to provoke clashes against moral aspects. This research aims to contribute to the reflection of the Oficina path through the lighting of the narratives of historical characters in question.This research intends to contribute to the reflection of the Oficina’s trajectory through the illumination of the narratives of the historical characters in question, the discussions about their engagements and the analysis of censorship processes that weighed on the group